2018
DOI: 10.31557/apjcp.2018.19.11.3175
|View full text |Cite
|
Sign up to set email alerts
|

Oxidants-Antioxidants Profile in the Breast Cancer Cell Line MCF-7

Abstract: Reactive oxygen species (ROS) have various biological effects and they are non-linear in characteristic. In high oxidative stress, they may cause cytotoxicity, inhibit cell proliferation, and induce cell death in the form of apoptosis/necrosis; while in low or medium oxidative stress, ROS may cause DNA damage, cell mutation, inflammation, cell proliferation, and eventually they may induce carcinogenesis. Antioxidants are compounds with the ability to reduce ROS. Cell line MCF-7 is one of the breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 10 publications
1
9
0
4
Order By: Relevance
“…Interestingly, MCF7 cells (ER pos ) showed an enhanced level of cell death induced by oxidative stress. This finding is in agreement with reports that MCF7 cells (ER pos ) are sensitive to oxidative stress which arises from their low endogenous levels of some antioxidants [ 48 ], which is further compounded by estrogen signaling [ 49 ]. In addition, like the majority of breast cancers, MCF7 cells express both ER and wildtype, functional p53, which renders MCF7 cells sensitive to cell death induced by oxidative stress [ 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, MCF7 cells (ER pos ) showed an enhanced level of cell death induced by oxidative stress. This finding is in agreement with reports that MCF7 cells (ER pos ) are sensitive to oxidative stress which arises from their low endogenous levels of some antioxidants [ 48 ], which is further compounded by estrogen signaling [ 49 ]. In addition, like the majority of breast cancers, MCF7 cells express both ER and wildtype, functional p53, which renders MCF7 cells sensitive to cell death induced by oxidative stress [ 49 , 50 , 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that cur T display the strongest DDPH (2,2-diphenyl-1-picrylhydrazyl) radical-scavenging activity comparing it to cur C. The lower IC 50 corresponds to the highest radical scavenging effectiveness observed with cur T. A lot of studies showed an important antioxidant effect of curcuma [14] and others concluded that this effect is due to Curcumin [13] but Curcuma contains other molecules that have the same effect [15].…”
Section: Discussionmentioning
confidence: 58%
“…The observed differences in compound 4e activity on MCF-7 tumor cells in comparison with normal fibroblasts HFF-1 may be due to the specific metabolic status of tumor cells, in which case an antioxidant compound with ROS scavenging properties, such as L-ASA, may have a cytotoxic effect; i.e., through a pro-oxidant effect on cancer cells associated with increase of ROS in tumor cells [55]. Particularly in MCF-7 cells, a small amount of an important cellular antioxidant enzyme manganese-dependent superoxide dismutase (MnSOD) was found in comparison with other cell lines [56]. It is therefore, possible that the compound 4e exerts a pro-oxidant activity in MCF-7 cells, which elevates the levels of ROS and induces cell death.…”
Section: Resultsmentioning
confidence: 99%